(untitled) (Bangladesh Journal of Agriculture, 2022)
The effect of temperature stress on the reproductive development and yield of five Brassica rapa was studied in a controlled growth chamber. The seeds of five Brassica genotypes namely BARI Sarisha-6, Tori 7, Kallayania, BARI Sarisha-9 and BINA Sarisha-4 were grown under day/night temperatures at 22/170C until early flowering or early siliqua development stage. The high temperature stress i.e., 28 /170C or 35/170C, both at early flowering stage and early siliqua formation stage were imposed for 7d and then allowed to recover at 22/170C for normal growth. Shoot dry matter accumulation varied with temperature and genotype. The highest shoot dry matter was recorded by Kallayania followed by BARI Sarisha-9. The optimum day temperature for seed yield of the main shoot showed closer to 280C. The largest seeds were produced in the 22/170C, the size, however, remained similar with 28/170C temperature stress. During this temperature regime, the highest seed yield was observed with BARI Sarisha-6 while BARI Sarisha-9 produced the lowest seed yield. Severe temperature stress (35/170C) reduced seeds per siliqua and 1000 seed weight in all genotypes. Maximum pollen viability and germination were recorded at 200C by Kallayania followed by Tori 7 at 250C. However, the temperature above 300C reduced pollen viability and germination for all the genotypes. In another set of treatments, the high temperatures exposure (28/230C) for 5d reduced oil content and increased protein concentrations. Plant exposed to 25/200C temperature stress showed significant changes in oleic, linoleic, and linolenic acids. The levels of saturated fatty acids were similar across the five genotypes in the control treatment, but palmitic acid and stearic acids increased with the temperature. Bangladesh J. Agri. 2019-2021, 44-46: 19-29